There can be no citizenship without information nor information without design - Redig, Joaquim (InfoDesign, 2004)
Initially, this paper seeks to emphasise how the creation of the SBDI has provided an important contribution to the development of Design in Brazil, while at the same time identifying those within the process at both a local and national levels. From this point on, the paper concentrates on analysing the constituting components of Information Design - the focus on the receiver, analogy, clarity, concision, emphasis, colloquial questions, opportunity, stability, amongst others - as well as observing how these elements participate in the communication process within the area of Design. By means of examples detected in the daily use of public information within our context, the paper also seeks to verify in which manner the presence or absence of these components contribute to the strengthening or weakening of the notion of citizenship.